PENINGKATAN KETERAMPILAN SISWA SLTA DI KECAMATAN LAWANG KIDUL DALAM PENGOLAHAN LIMBAH ORGANIK MENJADI KOMPOS DENGAN METODE TAKAKURA - Nuryanneti, Indra; Ghony, Muhammad Abdul; Zulatama, Apriansyah; Syaiful, M.; Zulfadly, Zulfadly (Gapenas Publisher, 2025)
Household organic waste, such as fruit peels and vegetable scraps, is one of the largest contributors to community waste. This activity aims to enhance the skills of high school students in Lawang Kidul District in processing organic waste using the Takakura method. This method involves an environmentally friendly, simple fermentation process to produce high-quality compost. The Community Service Program (PKM) is part of the Tri Dharma of Higher Education from the Bukit Asam Industrial Community Academy. The program was carried out through hands-on training that actively involved students. The results showed that students were able to understand and apply the Takakura method, resulting in good-quality compost. This program not only improved students' skills but also had a positive impact on the school environment